2017
DOI: 10.1177/1461444817731923
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying “Little Pink”: The creation and evolution of a gendered label for nationalistic activists in China

Abstract: In 2016, Little Pink has emerged as the label for a new wave of female-led cyber-nationalism in China. While increasingly popularized in media and online discourses, little is known about the evolution of this label and its significance for our understanding of China’s digital activism. This article takes the first step at unraveling the Little Pink mystery by examining its origins and contestation in China’s online community during the cross-strait memes war of 2016 when mainland nationalists mobilized to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 39 publications
3
88
1
1
Order By: Relevance
“…Through these public and semipublic digital sites, the authors observed activists in conversations with their friends, colleagues, opponents, and sometimes state agents. While anchoring our "residences" at significant websites and social media platforms (for example, @FeministVoices on Weibo), the authors had an open mindset to explore new links, sites, and information that echoed the "guerrilla ethnography" approach used in other studies on China's Internet (Yang 2003;Fang and Repnikova 2017). Most events and performances presented in this article were captured and documented in real time when they appeared on the digital sites, though we also provide detailed citations in endnotes for the readers to trace them online.…”
Section: Data and Method: Doing Online Ethnography In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Through these public and semipublic digital sites, the authors observed activists in conversations with their friends, colleagues, opponents, and sometimes state agents. While anchoring our "residences" at significant websites and social media platforms (for example, @FeministVoices on Weibo), the authors had an open mindset to explore new links, sites, and information that echoed the "guerrilla ethnography" approach used in other studies on China's Internet (Yang 2003;Fang and Repnikova 2017). Most events and performances presented in this article were captured and documented in real time when they appeared on the digital sites, though we also provide detailed citations in endnotes for the readers to trace them online.…”
Section: Data and Method: Doing Online Ethnography In Chinamentioning
confidence: 99%
“…The Chinese state exemplifies an authoritarian state's capacities of systematic information control (Mackinnon 2011;Spires 2011;Wang and Minzner 2015;Tsai 2016). The Chinese censorship system filters public information through both computation and human reading (King, Pan, and Roberts 2013), appropriates liberal messages for state propaganda (Fang and Repnikova 2017), blocks foreign social media platforms like Twitter and Facebook, and shuts down influential domestic websites, forums, and social media accounts. By censoring and deleting social movement webpages, symbols, and texts, censorship becomes a form of "coercive forgetting" that induces a public amnesia over collective action in the past and prevents activists from claiming their own history (Yang and Wu 2018, 4).…”
Section: The State's Presentation Of Self and Its Subversive Disruptionmentioning
confidence: 99%
“…For example, Rongbin Han's (2015) study on "voluntary fifty-center" sheds light on how, contrary to the state-deployed online commentators, certain constituency of netizens embark on the values of nationalism and rationality and undermine the moral and factual grounds of regime challengers, which ultimately work out to help stabilize the regime. Various scholarly studies on Internet commentators/fifty-cent party introduced in 2004 and professionalized in 2008 (Bandurski, 2008;Zheng, 2013), and Little Pink (Fang & Repnikova, 2017), also provide nuanced cases of either government-deployed or user-initiated systematic efforts to guide and influence public opinion on the Chinese Internet. Scholars harbor different views to the Chinese government's increasing vigilance toward online public opinion.…”
Section: The Rise Of Internet Public Opinion In Chinamentioning
confidence: 99%
“…This more intricate mentality has led to a higher degree of political engagement among the new generation of overseas Chinese students. Scholars believe that the emergence of such overseas patriotism was due to their insurmountable sojourner mentalities (Yan and Berliner, 2011), the crystalized long-term domestic patriotism education (Fang and Repnikova, 2018), and the increased salience of national identification under the status-based, loyalty-based, harmony-seeking, and utilitarian modes (Hail, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%